2022
DOI: 10.2215/cjn.06140522
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Symptom Trajectories in Nondialysis-Dependent CKD Patients

Abstract: Background and objectivesLate stages of CKD are characterized by significant symptom burden. This study aimed to identify subgroups within the 5-year trajectories of symptom evolution in patients with CKD and to describe associated patient characteristics and outcomes.Design, setting, participants, & measurementsAmong 2787 participants (66% men) with eGFR <60 ml/min per 1.73 m2enrolled in the CKD–Renal Epidemiology and Information Network (CKD-REIN) cohort study from July 2013 to May 2016, we assessed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Traditionally, the detection of kidney disease-related symptoms have used standardized questionnaires, such as the dialysis symptom index 2 or the kidney disease quality of life instruments, 15 administered to participants in trials or longitudinal cohorts. [4][5][6][7][8][9][10] These questionnaires are the gold standard for symptom ascertainment, but their use in routine clinical practice is impractical. We found that our results were generally consistent with findings of studies using standardized instruments, although symptoms seem to be under-recorded relative to dedicated patient surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the detection of kidney disease-related symptoms have used standardized questionnaires, such as the dialysis symptom index 2 or the kidney disease quality of life instruments, 15 administered to participants in trials or longitudinal cohorts. [4][5][6][7][8][9][10] These questionnaires are the gold standard for symptom ascertainment, but their use in routine clinical practice is impractical. We found that our results were generally consistent with findings of studies using standardized instruments, although symptoms seem to be under-recorded relative to dedicated patient surveys.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Fatigue, pain, nausea and vomiting, alterations in cognition, and others are highly prevalent. [4][5][6][7][8][9][10] Recent studies have examined symptom burden and trajectories in advanced CKD [5][6][7]9,10 and changes in symptoms during the transition from advanced CKD to dialysis. 4 However, the potential implications of detecting symptoms recorded in the electronic health record (EHR) using natural language processing (NLP), an artificial intelligence-based approach designed to detect difficult-to-quantify textual elements recorded by care clinicians, have not been well studied in patients with advanced kidney disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive symptoms data for this group of patients with advanced CKD are also informative, with most patients reporting fatigue (83%) and relatively few noting chest pain (24%). The distribution of symptom frequency over the study was relatively stable, with muscle pain, fatigue, itchy and dry skin, and poor appetite demonstrating a higher severity across the 5 years of the study (see Supplemental Figure 2 in [3]). These observations may provide potential therapeutic targets to change the trajectory for patients with advanced CKD.…”
mentioning
confidence: 99%
“…In this issue of CJASN , Faye et al applied a novel strategy to identify subgroups of symptom trajectories among patients with CKD in stages 3–5 within the French CKD–Renal Epidemiology and Information Network (CKD-REIN) cohort (3). The investigators followed 2787 patients to assess symptom burden related to CKD over a period of 5 years.…”
mentioning
confidence: 99%